Long-read assembly of the Brassica napus reference genome Darmor-bzh. Issue 12 (15th December 2020) - Rousseau-Gueutin, Mathieu; Belser, Caroline; Da Silva, Corinne; Richard, Gautier; Istace, Benjamin; Cruaud, Corinne; Falentin, Cyril; Boideau, Franz; Boutte, Julien; Delourme, Regine; Deniot, Gwenaëlle; Engelen, Stefan; et al.
Abstract: Background: The combination of long reads and long-range information to produce genome assemblies is now accepted as a common standard. This strategy not only allows access to the gene catalogue of a given species but also reveals the architecture and organization of chromosomes, including complex regions such as telomeres and centromeres. The Brassica genus is not exempt, and many assemblies based on long reads are now available. The reference genome for Brassica napus, Darmor-bzh, which was published in 2014, was produced using short reads and its contiguity was extremely low compared with current assemblies of the Brassica genus. Findings: Herein, we report the new long-read assembly of Darmor-bzh genome ( Brassica napus ) generated by combining long-read sequencing data and optical and genetic maps. Using the PromethION device and 6 flowcells, we generated ∼16 million long reads representing 93× coverage and, more importantly, 6× with reads longer than 100 kb. This ultralong-read dataset allows us to generate one of the most contiguous and complete assemblies of a Brassica genome to date (contig N50 > 10 Mb). In addition, we exploited all the advantages of the nanopore technology to detect modified bases and sequence transcriptomic data using direct RNA to annotate the genome and focus on resistance genes. Conclusion: Using these cutting-edge technologies, and in particular by relying on all the advantages of the nanopore technology, we provide the most contiguous Brassica napus assembly, a resource that will be valuable to the Brassica community for crop improvement and will facilitate the rapid selection of agronomically important traits.